Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) Oviposition Behavior in Previous Oviposition Situation - Lima, T. [UNESP]; Von Zuben, C. J. [UNESP] (Springer Nature, 2016)
Blowflies use their sense of smell to locate oviposition substrates and their vision to direct and assist in landing decision. Blowflies’ ovipositions are usually aggregated. Chrysomya megacephala (Fabricius) females, for example, prefer to lay eggs on substrates containing fresh eggs of the same species. However, it is possible that females would be capable of evaluating the substrate, reducing the size of egg cluster in sites with a high amount of eggs or larvae, or finding another site for laying their eggs, preventing the progeny from facing high competition for space and food. The present study aimed to investigate whether females of C. megacephala could distinguish and preferentially select previously infested substrates and whether females would lay their eggs attached or separate from eggs previously laid on the substrate. Behavioral measures were conducted inside cages under laboratory conditions in free-choice tests. Data analysis confirmed that C. megacephala females are able to distinguish the presence of cospecific eggs in the substrate and preferentially select previously infested substrates for egg laying, depositing their eggs separate from pre-existing large egg masses.
Keywords: Aggregated oviposition; blowflies; competition; egg mass; substrate selection